Thermal and Herbicide Tolerances of Chromerid Algae and Their Ability to Form a Symbiosis With Corals - Chakravarti, Leela J.; Negri, Andrew P.; van Oppen, Madeleine J. H. (Frontiers in Microbiology, 2019)
Reef-building corals form an obligate symbiosis with photosynthetic microalgae in the family Symbiodiniaceae that meet most of their energy requirements. This symbiosis is under threat from the unprecedented rate of ocean warming as well as the simultaneous pressure of local stressors such as poor water quality. Only 1 °C above mean summer sea surface temperatures (SSTs) on the Great Barrier Reef (GBR) can trigger the loss of Symbiodiniaceae from the host, and very low concentrations of the most common herbicide, diuron, can disrupt the photosynthetic activity of microalgae. In an era of rapid environmental change, investigation into the assisted evolution of the coral holobiont is underway in an effort to enhance the resilience of corals. Apicomplexan-like microalgae were discovered in 2008 and the phylum Chromerida (chromerids) was created. Chromerids have been isolated from corals and contain a functional photosynthetic plastid. Their discovery therefore opens a new avenue of research into the use of alternative/additional photosymbionts of corals. However, only two studies to-date have investigated the symbiotic nature of Chromera velia with corals and little is known about the coral-chromerid relationshiop. Furthermore, the response of chromerids to environmental stressors has not been examined. Here we tested the performance of four chromerid strains and the common dinoflagellate symbiont Cladocopium goreaui (formerly Symbiodinium goreauii, ITS type C1) in response to elevated temperature, diuron and their combined exposure. Three of the four chromerid strains exhibited high thermal tolerances and two strains showed exceptional herbicide tolerances, greater than observed for any photosynthetic microalgae, including C. goreaui. We also investigated the onset of symbiosis between and larvae of two common GBR coral species under ambient and stress conditions. Levels of colonisation of coral larvae with the chromerid strains were low compared to colonisation with C. goreaui. We did not observe any overall negative or positive larval fitness effects of the inoculation with chromerid algae vs. C. goreaui. However, we cannot exclude the possibility that chromerid algae may have more important roles in later coral life stages and recommend this be the focus of future studies.